2016
DOI: 10.5455/aim.2016.24.397-400
|View full text |Cite
|
Sign up to set email alerts
|

The Length of the Greater Palatine Canal in a Lebanese Population: a Radio-anatomical Study

Abstract: Objective:The aim of this study was to evaluate the length of the greater palatine canal in a Lebanese population using cone-beam computed tomography (CBCT) technology.Material and methods:In this study, we measured the length of 148 greater palatine canals in 74 CBCT images of Lebanese adult patients (38 females and 36 males). The data obtained was analyzed statistically to determine 1) if age is related to the length of the canal, 2) if the length of the left side tends to be systematically larger or smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The results of the meta-analysis regarding other characteristics of the GPC are presented in Table 8 . A total of 13 studies [ 3 , 4 , 23 , 25 , 34 , 35 , 50 , 52 , 59 , 67 , 70 , 75 , 76 ] ( n = 4,798 subjects) reported data on the length of the greater palatine canal. The pooled mean, across the 13 studies, was calculated to be 26.97 mm (95% CI = 23.65–30.29 mm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the meta-analysis regarding other characteristics of the GPC are presented in Table 8 . A total of 13 studies [ 3 , 4 , 23 , 25 , 34 , 35 , 50 , 52 , 59 , 67 , 70 , 75 , 76 ] ( n = 4,798 subjects) reported data on the length of the greater palatine canal. The pooled mean, across the 13 studies, was calculated to be 26.97 mm (95% CI = 23.65–30.29 mm).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3 studies [ 3 , 25 , 59 ] ( n = 360) reported data on the anteroposterior diameter of the upper opening of the greater palatine canal. The pooled mean, across the three studies, was calculated to be 3.88 mm (95% CI = 3.77–3.99 mm).…”
Section: Resultsmentioning
confidence: 99%